Enhancing stability and voltage quality in remote DC microgrid systems through adaptive droop control approach - Lam, Hong Phuc; Nguyen, Hung Duc; Pham, Minh Duc (Institute of Advanced Engineering and Science, 2024)
To ensure the stable and accurate operation of